2012
DOI: 10.3189/2012aog60a005
|View full text |Cite
|
Sign up to set email alerts
|

Basal crevasses and associated surface crevassing on the Larsen C ice shelf, Antarctica, and their role in ice-shelf instability

Abstract: We identify a series of basal crevasses along a 31 km transect across the northern sector of the Larsen C ice shelf, Antarctica, using in situ ground-penetrating radar. The basal crevasses propagate from a region of multiple, shallow basal fractures to form widely spaced (0.5-2.0 km) but deeply incised (70-134 m) features. Surface troughs, observed in visible imagery, exist above the basal crevasses as the ice vertically shears to reach hydrostatic equilibrium, while widespread surface crevassing occurs along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 49 publications
2
90
0
Order By: Relevance
“…LAIS and LBIS both accelerated before collapsing (Bindschadler et al, 1994;Rignot et al, 2004), and LBIS apparently collapsed after weakening of the shear zones between ice flow units (Khazendar et al, 2007;Vieli et al, 2007;Glasser and Scambos, 2008). The shear zones in LCIS are less strongly sheared (Khazendar et al, 2011) and hence more stable, but the ice is already quite damaged (Jansen et al, 2010;McGrath et al, 2012;Borstad et al, 2013). The uncertainties in this interaction are large and we are unable to assess a timescale for this risk.…”
Section: Crevassing Weakens Shear Zonesmentioning
confidence: 86%
“…LAIS and LBIS both accelerated before collapsing (Bindschadler et al, 1994;Rignot et al, 2004), and LBIS apparently collapsed after weakening of the shear zones between ice flow units (Khazendar et al, 2007;Vieli et al, 2007;Glasser and Scambos, 2008). The shear zones in LCIS are less strongly sheared (Khazendar et al, 2011) and hence more stable, but the ice is already quite damaged (Jansen et al, 2010;McGrath et al, 2012;Borstad et al, 2013). The uncertainties in this interaction are large and we are unable to assess a timescale for this risk.…”
Section: Crevassing Weakens Shear Zonesmentioning
confidence: 86%
“…Khazendar et al (2011) noted that rifts and other fractures were linked to large spatial variations in the inferred rheology of the shelf. Several recent studies of the ice shelf have observed basal crevasses along longitudinal transects of the shelf using ground-penetrating radar (McGrath et al, 2012;Luckman et al, 2012), indicating that basal crevasses are likely widespread on the ice shelf.…”
Section: Application To Larsen C Ice Shelfmentioning
confidence: 99%
“…Schoof, 2007), which has motivated a number of recent numerical studies of the relationship between ice shelf buttressing and grounding line stability for a marine ice sheet (Goldberg et al, 2009;Gagliardini et al, 2010;Favier et al, 2012;Gudmundsson, 2013). However, in spite of the widespread recognition of the importance of fractures for the flow and stability of ice shelves (e.g Jezek et al, 1985;Doake and Vaughan, 1991;Vaughan, 1993;van Der Veen, 1998a;Scambos et al, 2000;Kenneally and Hughes, 2004;Larour et al, 2004a;Glasser et al, 2009;Khazendar et al, 2009;Jansen et al, 2010;Albrecht and Levermann, 2012;Luckman et al, 2012;McGrath et al, 2012), little attention has been given to the impact of fractureinduced weakening on ice shelf buttressing.…”
Section: Introductionmentioning
confidence: 99%
“…1) (Luckman et al, 2012;McGrath et al, 2012;Jansen et al, 2013;Kulessa et al, 2014;McGrath et al, 2014). Surveys were carried out using antennas of different frequencies (25, 100, or 200 MHz) depending on the field campaign.…”
Section: Ground-penetrating Radarmentioning
confidence: 99%